2021
DOI: 10.1002/anie.202015625
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Cell Surface Conjugation of Nanoparticles by a Combination of Metabolic Labeling and Click Chemistry

Abstract: Conjugation of nanoparticles (NP) to the surface of living cells is of interest in the context of exploiting the tissue homing properties of ex vivo engineered T cells for tumor‐targeted delivery of drugs loaded into NP. Cell surface conjugation requires either a covalent or non‐covalent reaction. Non‐covalent conjugation with ligand‐decorated NP (LNP) is challenging and involves a dynamic equilibrium between the bound and unbound state. Covalent NP conjugation results in a permanently bound state of NP, but t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 25 publications
1
31
0
Order By: Relevance
“…Through various techniques that can be largely classified into two categories, noncovalent and covalent, NPs can be attached on cell surfaces without being internalized by the macrophage carrier, and transported to tumor sites (110)(111)(112)(113)(114)(115)(116). Table 1 briefly describes the categories, principles, and mechanisms of major NP delivery methods with live macrophages, and readers are directed to more detailed reviews on this subject (112,123,134). Table 1 also includes the methods of loading NPs in macrophagederived cell membranes or extracellular vesicles, which will be discussed in the following section.…”
Section: Engineering Macrophages For Np Delivery In Cancer Therapy Np Loading In Macrophagesmentioning
confidence: 99%
“…Through various techniques that can be largely classified into two categories, noncovalent and covalent, NPs can be attached on cell surfaces without being internalized by the macrophage carrier, and transported to tumor sites (110)(111)(112)(113)(114)(115)(116). Table 1 briefly describes the categories, principles, and mechanisms of major NP delivery methods with live macrophages, and readers are directed to more detailed reviews on this subject (112,123,134). Table 1 also includes the methods of loading NPs in macrophagederived cell membranes or extracellular vesicles, which will be discussed in the following section.…”
Section: Engineering Macrophages For Np Delivery In Cancer Therapy Np Loading In Macrophagesmentioning
confidence: 99%
“…Examples include the use of liposomes for targeted delivery [ 41 , 67 ] and methods that exploit enzymatic ‘uncaging’ of inactive MOE precursors at a target site [ 68 ]. Such cell type specific approaches can in turn serve as a targeting strategy for the selective delivery of nanoparticles carrying, for example, imaging agents or therapeutics [ 69 , 70 ].…”
Section: Metabolic Oligosaccharide Engineeringmentioning
confidence: 99%
“…in industry as well as in academia. Thus, after the independent selective synthesis of 1,4-disubstituted triazoles by Sharpless–Fokin and Meldal using Cu­(I) compounds as catalysts, considerable attention has been given to the CuAAC reaction. It has been observed that any Cu­(I) source may act as a catalyst for the CuAAC reaction. , Generally, an easily available Cu­(II) source like CuSO 4 by the chemical reduction of sodium l -ascorbate was used to generate the Cu­(I) catalyst . However, this type of Cu source is not desirable because the Cu­(I) oxidation state is very unstable; it may disproportionate to Cu(0) and Cu­(II) or may get oxidized to its Cu­(II) compound. ,, Thus, a larger quantity of Cu­(II) compound is required for the selective synthesis of triazoles .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in electronics and biomedicine applications, removal of copper ions is a problem. , It has been shown that ancillary ligand coordinated Cu­(I) complexes can decrease the catalyst loading and increase the selectivity of the CuAAC reaction, as these Cu­(I) complexes are more stable. ,, Employing this strategy, Astruc et al have reported amphiphilic and dendrimer nanoreactors, Uozumi et al have reported amphiphilic self-assembled polymers, Zimmerman et al have reported a metal–organic nanoparticles for parts-per-million (ppm) Cu­(I) catalysis in water. However, though a library of Cu­(I) complex catalyzed CuAAC reaction is known, such catalysis in water at a low ppm catalyst loading is still rare. As Cu­(I) is the lower oxidation state of copper, it is important to use a strong π-acceptor-type chelating ligand for the development efficient catalyst for CuAAC reactions. Here, we report a series of amine-functionalized azo-aromatic copper­(II) complexes (Scheme A) that showed interesting ligand hemilability upon reduction, and the reduced Cu­(I) complexes are highly efficient (up to low ppm level catalysis) for selective CuAAC reaction via intramolecular acid–base cooperation solely in water under air (Scheme B).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation